Molecular and evolutionary determinants for protein interaction within a class II aldolase/Adducin domain - Marina E. Seheon; Amalia S. Parra; Christopher A. Johnston (PLoS ONE, 2025)
The appearance of modular protein interaction domains represents a crucial step in the evolution of multicellularity. For example, the class II aldolase domain (ALDO DOM ) found within the Adducin gene family shares sequence and structural homology to a glycolytic aldolase enzyme found in many evolutionarily ancient phyla. ALDO DOM is best known for direct binding to actin filaments through a tetrameric assembly lacking catalytic activity. Molecular details for additional ALDO DOM interactions have not been resolved, nor have the sequence changes underlying the dramatic functional switch in the aldolase protein fold. Here we explore the molecular basis for the interaction between ALDO DOM of Hts ( Drosophila Adducin) and the mitotic spindle regulator, Mud. Our results suggest a distinct mode of interaction, as conserved actin-contacting residues on the tetramer surface were found dispensable for Mud binding. Instead, we identify a critical role for the ALDO DOM C-terminal helix (CThelix), along with residues from the adjacent protomer that occur at a tetrameric interface conserved among domains and a subgroup of aldolase enzymes (ALDO ENZs ). Truncation of the CThelix from bacterial ALDO ENZ , or chimeric fusion with that from Hts, confers ALDO DOM -like Mud binding. Sequence database analyses suggest ALDO DOM function may have arisen in the primitive metazoan phylum, Placozoa , which contains both an aldolase enzyme and domain capable of Mud binding. Finally, we identify a single, conserved arginine-to-glycine change that also permits Mud binding within the bacterial ALDO ENZ . Our work provides molecular and evolutionary insights into the function of a conserved protein-binding domain within multicellular organisms.